A Randomized Double-Blind Placebo-Controlled Trial of Fruit and Vegetable Concentrates on Intermediate Biomarkers in Head and Neck Cancer. (March 2018) - Datta, Mridul; Shaw, Edward G.; Lesser, Glenn J.; Case, L. Douglas; Vitolins, Mara Z.; Schneider, Charles; Frizzell, Bart; Sullivan, Christopher; Lively, Mark; Franzmann, Elizabeth; Hu, Jennifer J.
Background. Head and neck cancer (HNC) patients are at an increased risk for developing second primary tumors (SPTs). Diets rich in fruits and vegetables (FVs) may lower HNC risk. FV concentrates may offer a potential alternative to increasing FV intake. Methods. We conducted a randomized, double-blind, placebo-controlled trial to evaluate whether Juice PLUS+ (JP; a commercial product with multiple FV concentrates) has an effect on p27 and Ki-67, biomarkers associated with the risk of SPTs. During 2004-2008, we randomized 134 HNC patients to 12 weeks of JP (n = 72) or placebo (n = 62). Oral cavity mucosal biopsies and whole blood were obtained at baseline and after 12 weeks. All participants were given the opportunity to receive JP for 5 years following the end of the intervention period, and they were followed yearly for the development of SPTs. Results. After 12 weeks, patients on JP had significantly higher serum α-carotene ( P = .009), β-carotene ( P < .0001), and lutein ( P = .003) but did not differ significantly in p27 ( P = .23) or Ki-67 ( P = .95). JP use following the initial 12-week trial was not significantly associated with SPT prevention. Conclusions. Despite increased serum micronutrient levels, our results do not suggest a clinical benefit of JP in HNC patients. Future studies should focus on longer intervention periods and/or modified supplement formulations with demonstrated chemopreventive properties.